George F. Handel - Thomson, James, 1789-1850 (engraver):::Creator::::::::::::; Hudson, Thomas, 1701-1779 (artist):::Contributor:::::::::::: (William Mackenzie; Glasgow; Scotland)
Engraving of G.F. Handel by James Thomson after painting by Thomas Hudson.